Diabetic Nephropathy: Role of Toll-like Receptors and Notch Pathway - Najah R. Hadi; Saad Rasool Shaker (Diabetic Nephropathy: Role of Toll-like Receptors and Notch Pathway, 2022)
Diabetes mellitus and its complications are becoming one of the most important health problems in the world. Diabetic nephropathy is now the main cause of end-stage renal disease. The intended aim during the management of diabetes is to maintain blood glucose close to normal because the majority of patients have poor control of their elevated blood glucose and are highly prone to severe macrovascular and microvascular complications. Toll-like receptors are transmembrane proteins that transfer the antigen recognition information from outside to inside of the cell as a factor in the immune reaction. Activation of the innate immune system via toll-like receptors (TLRs) is implicated in the pathogenesis of insulin resistance, diabetic nephropathy, and atherosclerosis. Recent studies indicate that Notch plays a key role in establishing proximal epithelial fate during nephronsegmentation as well as the differentiation of principal cells in the renal collecting system. Notch signalling is markedly reduced in the adult kidney; however, increased Notch signalling has been noted in both acute and chronic kidney injuries. Increased glomerular epithelial Notch signalling has been associated with albuminuria and glomerulosclerosis, while tubular epithelial Notch activation caused fibrosis development most likely inducing an improper epithelial repair pathway. Recent studies thereby indicate that Notch is a key regulator of kidney development, repair, and injury.